Effect of chip formation on tool wear in machining of titanium - Lee, Ka Hung (2010)
Nowadays, titanium has become an important material mainly used in engineering application because of its excellent mechanical and physical property, for example, aircraft, aero-engines, biomedical devices and components in chemical processing equipments. However, the machining of titanium is getting tougher as tool wear is a common phenomenon happened during machining operations due to the frictions and forces produced when the cutting tool is in contact with the workpiece. The kind of chips produced from the machining operation may contribute to certain tool wear and cause the cutting tool life to be lowered. So, it is necessary to find out the optimum machining parameters that produce certain chip structure formations with lowest tool wear rate. Therefore, this project gives an investigation on the effect of chip formation on tool wear in machining of Titanium. The experiments will be carried out using a Computer Numerically Controlled machine (CNC). Different value of cutting speeds and feed rates are selected in order to study and observe the kind of chip formed. The cutting speed selected in the experiment are 90, 120 and 150 m/min, while the feed rates range from 0.05 to 0.15 mm/min. Apart from that, the depth of cut is kept constant at 0.5 mm. The diameter and length of titanium used in this study are 25 mm and 200 mm respectively. The chips collected from all these machining parameters will be taken to several chip preparation processes and then examined using optical microscope. Lastly, these data will be tabulated into graphical form as to clearly show the relationship between the variables and tool wear. The result shows that the shear layer thickness of the chip is the significant parameter that influences the tool wear relatively. The higher the shear layer thickness, the lower the tool wears, and vice versa. From the experiments, the shear layer thickness is proved as affected by the cutting speed and feed rate significantly. The lowest tool wear (crater and flank wear are 7.8921 μm and 1.2162 μm respectively) was determined at shear layer thickness of 0.0123 μm, which machined with cutting speeds of 162.4264 m/min and feed rate of 0.1 mm/rev.